Implementation of Polygamy Law According to the Perspective of Islamic Law and Human Rights: Case Study in Bireuen Regency - M Nur, Abdullah; Bardan, Fadhilah; Razali, Ruslan; Abdurrauf, Mursal; Sulaiman, Mursalin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Polygamy is a practice permitted under Islamic law with certain conditions, but it often reaps controversy in the context of human rights (HAM). This article examines the implementation of polygamy law in Bireuen Regency, Aceh, by examining the applicable sharia regulations and how their implementation is in line with or contrary to human rights principles. This study uses a descriptive qualitative method with a case study approach. Data were obtained through interviews, documentation, and literature studies. The results of the study show that although polygamy is strictly regulated by sharia law and local government regulations, in practice there are still various violations of women's rights, such as lack of consent from the first wife and minimal protection of justice in the household.